البدعة و موقف السنة النبوية منها نبذة عن الرسال - Rahima Sikumbang (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
Maintaining the purity of the source of Islamic shari'ah from the irresponsible person is something urgent, and always done by salafusshalihin scholars since the time of the prophet. Bid.ah has existed in the time of the Prophet, and progressed in the days of companions, and the tabi'in until now. Islam, from the point of worship of its nature tauqifiyyah, (fixed and certain)), should be based on shari'ah which has been determined by AlQuran, Assunnah, Qiyas, and the agreement of scholars. If the worship done without shari'ah, it is pertained as bid'ah. In accordance with the hadith of the Prophet narrated in the book of Muslim Sahih Bukhari: